Prevalence of Endoscopy at Idris Teaching Hospital Sialkot Medical College, Sialkot (Medical Forum Monthly, 2020)
Objective: To study Prevalence of Endoscopy At Idris Teaching Hospital Sialkot Medical College Sialkot.Study Design: Experimental and Observational studyPlace and Duration of Study: This study was conducted at Idris Teaching Hospital Sialkot during Jan 2018 to July 2019.Materials and Methods: This study comprises 1021 patients undergoing endoscopic examination.The demographic data was noted down and lab tests were also advised for example hepatitis A, B and C HIV. Written informed consent was also taken from every patient before the start of the endoscopic examination. The Permission of ethical committee was also considered before collection of data and get publishing in the medical journal. The results were analyzed on SPSS version 10.Results: Mean Age was 45.34 years and SD(standard deviation) was 16.23 years. At the age of 10-20years , there were 50(10.18%) male and 51(9.62%) female of endoscopy were included in this study. At the age of 21-30 years there were 101(20.57%) male and 85(16.04%) females. At the age of 31-40 years there were 100(20.36%) male and 75(14.15%) female, At the age of 41-50 years there were 101(20.57%) male and 130(24.52%) female , at the age of 51-60 years there were 25(5.09%)Male and 75(14.15%) female , At the age of 61-70 years there were 75 (15.27%) male and 85(16.04%) female, at the age 70 years and above there were 35(7.12%) Male and 29(5.47%) females patients were included in the study. It was observed that female patients of endoscopy were more prevalence than male patients. It was observed that there were 175(35.64%) Male and 201(37.92%) female patients at the high socioeconomic status , in the middle socio economics status there were 187(38.10%) Male and 210(39.62%) female , in the low socio economic status there were 129(26.27%) Male and 119(22.45%) female patients of endoscopy were found in this study. It was observed that there were more patients of endoscopy in middle class than high gentry and lower class. From urban area, there were 230(46.84%) Male and 300(56.61%) female and from rural area 261(53.15%) male and 230(43.40%) female patients of endoscopy were observed in this study. It was also observed there was more prevalence of endoscopy patients from rural area than urban area.Conclusion: Esophagogastroduodenoscopy is the only reliable tool for correctly determining the etiology of UGIB. We observed esophageal varices as the main cause of UGIB in our setup which is similar to those in local literature but different from those in western literature. Predominance of varices as a cause of acute UGIB reflects high prevalence of CLD due to viral hepatitis.